Swallowed dentures in thoracic oesophagus - Chakrabarty, Ushnish; Datta, Swarnendu; Pal, Madhusudan (International Surgery Journal, 2020)
Oesophagus is the second most (46.8%) common site of impaction of foreign body in the gastro-intestinal tract. Dentures constitute the 3rd most common (2.4%) foreign body in oesophagus of adults, following meat bone (76.1%) and coin (3.6%).In our Institute, impacted dentures in esophageal are referred to our department after a failed endoscopic venture at removal by ENT surgeons. Extraction in such a situation calls for judicial planning and careful timing of the procedure to achieve satisfactory results. The present study was done on 11 cases of thoracic oesophageal dentures which were removed surgically in the Department of CTVS Medical College and Hospital, Kolkata over 2 years of period. Between 1st October 2017 to 30st September 2019, 11 dentures were extracted from thoracic oesophagus via right postero-lateral thoracotomy approach. The defect in the oesophagus after denture removal was primarily closed; with reinforcement using intercostals muscle pedicled flap. A defunctioning cervical oesophagostomy and a feeding jejunostomy (FJ) were done in all cases. Surgical leaks were noted in 5 cases, of which 1 lady had fulminant mediastinitis before she died. Pneumonia was observed in 4 cases, superficial surgical wound infection in 2 cases, blocked FJ tube in 1 case and leakage following closure of cervical oesophagostomy in 3 cases. Thoracic esophageal dentures are serious surgical entities which need early diagnosis and management. Pre-operative optimization is very important for avoiding surgical leakage.